Strategi Branding Manggis melalui Media Sosial sebagai Upaya Pemberdayaan Petani - Fatah, Muhammad Ghoni Abdillah; Mahbubah, Surotul; Fariza, Dita Sari Rofi’u; Ma’suq, Ahmad Tarajjil; Hidayatullah, Syarif; Salsabila, Fina Fathiya; Qomariyah, Lailatul; Patriolika, Erika; Maharani, Karlina Dewi; Ismahayati, Dewi; Cahyani, Budiato; Hidayatullah, Wasil; Sulfa, Indana; Al Hayaza, M. Iqbal; Sari, Dewi Indah; Wazis, Kun (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2024)
Mangosteen is one of the largest commodities in Kaliglagah Village, Jember, and branding efforts are required to enhance its recognition and establish its identity. Social media was chosen as a strategic platform for branding, aiming to promote the mangosteen and its advantages while empowering farmers and improving the village’s economy. This study employed a Participatory Action Research (PAR) approach, engaging local communities and leaders in learning, problem-solving, and social change. Although Kaliglagah mangosteen is of premium quality, it lacks a strong identity as a signature product of Jember. Branding strategies were implemented through Blogspot, Instagram, and Facebook platforms, involving collaboration with farmers, farmer groups, and the village government. Activities included problem identification, collaborative planning, communication with agricultural authorities, and branding execution via social media. These efforts aim to expand markets, strengthen local identity, and support farmer empowerment. Evaluations showed positive responses, although improving digital literacy among farmer groups remains necessary for optimal results. Keywords: Branding Strategy, Social Media, Farmer Empowerment Abstrak: Manggis merupakan salah satu komoditas terbesar di Desa Kaliglagah, Jember, yang membutuhkan upaya branding agar lebih dikenal dan diakui. Media sosial dipilih sebagai sarana strategis untuk branding, dengan harapan memperkenalkan manggis beserta keunggulannya, sekaligus memberdayakan petani dan meningkatkan perekonomian desa. Penelitian menggunakan pendekatan Participatory Action Research (PAR), melibatkan masyarakat dan tokoh lokal dalam pembelajaran, pemecahan masalah, dan perubahan sosial. Meskipun manggis Kaliglagah memiliki kualitas unggulan, identitasnya sebagai produk khas daerah Jember belum kuat. Strategi branding dilakukan melalui platform seperti Blogspot, Instagram, dan Facebook, melibatkan kolaborasi dengan petani, kelompok tani, dan pemerintah desa. Kegiatan meliputi identifikasi permasalahan, perencanaan kolaboratif, komunikasi dengan dinas pertanian, dan pelaksanaan branding melalui media sosial. Upaya ini diharapkan memperluas pasar, memperkuat identitas lokal, dan mendukung pemberdayaan petani. Evaluasi menunjukkan respons positif, namun peningkatan literasi digital kelompok tani tetap diperlukan. Kata kunci: Strategi branding, Media sosial, Pemberdayaan petani